“TOP TEN”, CITRA RELASIONAL MANUSIA DALAM “TRIAS ENTITAS” TINJAUAN KRITIS-DIALOGIS PANDANGAN BUBER DAN HEIDEGGER - Bruno Rumyaru (President University, 2018)
ABSTRACT. Human existence shows that there are self-tension and identity crisis. This background displays thathumans have been searching for the answers to their essence and meanings for their own existence. There is aparadoxical phenomenon in the lives of humans. On one hand, humans have made effort to fulfill their needs andtendencies through all of their artificially earned achievements and attributes. On the other hand, the variousforms of existential realization have created existential tension. Human existence shows a dilemmatic relaity.Humans have caused for their own self-alienation. Why does this human existensial paradoxical phenomenon hasto occur? Critical Realism Method used in this qualitative study made effort to answer this central question byrevealing the human ontological-existential image based on the dialogical-critical review on Martin Buber andMartin Heidegger’s philosophical thoughts. The result of this study emphasizes on human’s relational “Top Ten”,which eventually leads to the basic principles of “Trias Entitas” as the identity for each human existence.